The Curative Innovation of Novel Triple-Drug Compared to Double-Drug Regimen in Lymphatic Filariasis: A Systematic Review - Ruby, Rivaldi; Arifin, Erlangga Saputra; Charens (Indonesian Journal of Tropical and Infectious Disease, 2022)
The World Health Organization has established a global program for the elimination of lymphatic filariasis by 2020; recent data has shown an impracticable result accomplishing it. Therefore, this study aims to identify the efficacy and safety between triple-drugs (DEC, ALB, IVM) and double-drugs (DEC & ALB/IVM & ALB) for lymphatic filariasis treatment. A systematic review was conducted with Preferred Reporting Items for Systematic Reviews and Meta-analysis (PRISMA) statement guidelines. The literature search was done using five databases: PubMed, ProQuest, ScienceDirect, EBSCO, and CENTRAL until December 3, 2020 without any publication date range imposed. Data collection was done by three independent reviewers and entered into a predesigned data extraction form. Cochrane risk of bias tool 2.0 was utilized in the quality assessment of the studies. Search strategies identified 209 studies. Three relevant full-text articles met our inclusion criteria. Overall studies had low risk of bias. The main findings are as follows: (a) Administration of single dose of triple-drug regimen resulted in a total elimination of microfilaria 12 months after treatment whilst 91% participants given with double-drug remained microfilaremic (p=0.002); (b) In larger samples (n=182), triple drug cleared microfilaria in 96% of the participants and only 32% of the participants receiving double-drug regimen after 12 months observation; (c) Statistically, the triple-drug safety has a lower degree than the double-drug regimen (p=0.02). The triple-drug treatment has a better efficacy compared to the double-drug regimen in treating lymphatic filariasis. Furthermore, both regimens are proven safe with no serious adverse events elicited.